Fast and simultaneous detection of heavy metals using a simple and reliable microchip-electrochemistry route: An alternative approach to food analysis - Chailapakul O. (2014)
This paper reports, for the first, the fast and simultaneous detection of prominent heavy metals, including: lead, cadmium and copper using microchip CE with electrochemical detection. The direct amperometric detection mode for microchip CE was successfully applied to these heavy metal ions. The influences of separation voltage, detection potential, as well as the concentration and pH value of the running buffer on the response of the detector were carefully assayed and optimized. The results clearly show that reliable analysis for lead, cadmium, and copper by the degree of electrophoretic separation occurs in less than 3 min using a MES buffer (pH 7.0, 25 mM) and l-histidine, with 1.2 kV separation voltage and -0.8 V detection potential. The detection limits for Pb2+, Cd2+, and Cu2+ were 1.74, 0.73 and 0.13 μM (S/N = 3). The %R.S.D. of each peak current was <6% and migration times <2% for prolonged operation. To demonstrate the potential and future role of microchip CE, analytical possibilities and a new route in the raw sample analysis were presented. The results obtained allow the proposed microchip CE-ED acts as an alternative approach for metal analysis in foods. © 2007 Elsevier B.V. All rights reserved.